A Numericl Version of Three Classical Papers - Abdurakhmanov, Abdurasul (Université d'Ottawa | University of Ottawa, 2002)
A numerical two-country Diamond type of overlapping-generations model is developed to test the theoretical propostions derived in Buiter (1981), Blanchard (1985), and Assaf R. and Frenkel J. (1992). The paper first derives main proposition of these papers